Distance aware transmit antenna selection for massive MIMO systems - Chura , Shenko; Negash, Yalemzewd; Wondie , Yihenew (Zede Journal of Ethiopian Engineers and Architects, 2023)
Multiple-Input Multiple-Output (MIMO) antenna selection is a signal processing techinique by which the Radio Frequency (R.F.) chain components are switched to their corresponding subset of antennas. Antenna selection revolves the complexity and power consumption of R.F. transceivers. This paper proposes an optimal antenna selection technique for multiple radio component type massive MIMO, which combines two selction techniques by exploiting the minimum signal-to-noise ratio (SNR) at the cell edge and dynamic channel condition due to mobility. After an adaptive selection has been made, the same number selection has been made, the same number of R.F. components are active, and the rest are set to sleeping mode to apply fractional transmit power re-allocation at sub 6GHz and mm Wave frequencies. Accordingly, the branch with better signal quality among the array is chosen and added in iteration till the selected value is attained; however, re-selection still boosts E.E. at the cost of the total rate. The results show that the algorithm over performs the random selection, achieving better energy efficiency that full array utilization and random selection. Moreover, capacity reduction due to selection is compensated by applying nonlinear preceding at the cost of complexity.